2015
DOI: 10.1051/kmae/2015017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cytochrome oxidase I gene analysis indicates a restricted genetic background in Finnish noble crayfish(Astacus astacus)stocks

Abstract: Key-words:noble crayfish, native species, population decline, genetic diversity, cytochrome oxidase IThe IUCN Red List indexes the noble crayfish (Astacus astacus) as vulnerable, with a declining population trend. The main threats to the species are the crayfish plague caused by the oomycete Aphanomyces astaci and the introduced North American crayfish that act as the carriers of this disease. In Finland, the noble crayfish is considered as a native species, which original distribution area covers the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Moreover, genetic structure of studied A. astacus population revealed by microsatellites indicated that populations in the western part of the Balkans harbour important components of genetic diversity for the species as anticipated in the previous studies (Schrimpf et al, 2011;Schrimpf et al, 2014;Schrimpf et al, 2017;Gross et al, 2013;Laggis et al, 2017). The finding of population structuring at both local, and larger geographic scales in this study is consistent with other studies of A. astacus across its distribution range (Schrimpf et al, 2011;Schrimpf et al, 2014;Schrimpf et al, 2017 Makkonen, Kokko & Jussila, 2015;Bláha et al, 2016;Laggis et al, 2017;Mrugała et al, 2017;Panicz et al, 2019). Astacus astacus is characterised by the complex evolutionary history as it has a large distributional range across a number of large catchments, and phylogeographic patterns and genetic diversity shaped through past geo-climatic processes and recent anthropogenic activities (translocations, reintroductions) (Kouba, Petrusek & Kozák, 2014;.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, genetic structure of studied A. astacus population revealed by microsatellites indicated that populations in the western part of the Balkans harbour important components of genetic diversity for the species as anticipated in the previous studies (Schrimpf et al, 2011;Schrimpf et al, 2014;Schrimpf et al, 2017;Gross et al, 2013;Laggis et al, 2017). The finding of population structuring at both local, and larger geographic scales in this study is consistent with other studies of A. astacus across its distribution range (Schrimpf et al, 2011;Schrimpf et al, 2014;Schrimpf et al, 2017 Makkonen, Kokko & Jussila, 2015;Bláha et al, 2016;Laggis et al, 2017;Mrugała et al, 2017;Panicz et al, 2019). Astacus astacus is characterised by the complex evolutionary history as it has a large distributional range across a number of large catchments, and phylogeographic patterns and genetic diversity shaped through past geo-climatic processes and recent anthropogenic activities (translocations, reintroductions) (Kouba, Petrusek & Kozák, 2014;.…”
Section: Discussionsupporting
confidence: 92%
“…The most likely postglacial colonization route of A. astacus towards north and central Europe was through the Danube River system (Schrimpf et al, 2014;Laggis et al, 2017). Also, human activities, such as translocations and re/introductions of A. astacus, also probably strongly influenced the natural genetic structure and diversity (e.g., population mixing and introgression between introduced and indigenous populations) across Europe (Souty-Grosset & Reynolds, 2009;Schrimpf et al, 2011;Schrimpf et al, 2014;Gross et al, 2013;Gross et al, 2017;Makkonen, Kokko & Jussila, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Combining mitochondrial DNA (mtDNA) sequences and microsatellite data, they concluded that the North Sea and Baltic Sea basins in Northern Europe were likely to have been colonized independently via different paths from a common refugium in the eastern Black Sea basin, although only two Fennoscandian samples (both from Finland, with no samples from southern Sweden) were analysed. In a comprehensive follow-up study of mtDNA variation (cytochrome oxidase I gene, COI) in Finland and Estonia, Makkonen et al (2015) found fixation for the same haplotype as observed by Schrimpf et al (2014) in their Finnish samples. These results are not in conflict with our suggestion of two independent colonization events to the Baltic Sea basin.…”
Section: Postglacial Colonizationmentioning
confidence: 77%
“…Subsequent studies have focused mainly on intraspecific genetic variation in continental Europe (but see Makkonen, Kokko, & Jussila, 2015). Schrimpf et al (2014) presented evidence for two separate areas in south-eastern Europe used as refugia by noble crayfish during the last glaciation period and have suggested that the North Sea and the Baltic Sea basins were probably recolonized independently from one of these refugia, the Eastern Black Sea basin, via different colonization routes.…”
Section: Introductionmentioning
confidence: 99%
“…They have even been used as food during fasting within religious communities, in order to bypass regulations forbidding the consumption of animals during fasting (e.g., Swahn, 2004;Ackefors, 2005;Patoka et al, 2016b) and also as a source of additional income for people catching and marketing them to bourgeois and religious communities (e.g., Lehtonen, 1975;Bohman et al, 2006;Gherardi, 2011). Trading frequently included crayfish transport over long distances (Anon, 1899;Edsman and Schröder, 2009;Jussila et al, 2013b) resulting in a mix of the natural genetic composition of native species (e.g., Edsman et al, 2002;Makkonen et al, 2015). Moreover, by trading live alien crayfish species within Europe, the spreading of the crayfish plague pathogen A. astaci was facilitated around the continent, as crayfish were often placed in water bodies along the way to markets (e.g., Alderman, 1996).…”
Section: Introductionmentioning
confidence: 99%